Pengembangan Sistem Informasi Geografi Bencana Alam Pada Kabupaten Madiun Berbasis Web Menggunakan Metode Build and Fix - Ezra Gayu; Pradityo Utomo; Dwi Nor Amadi (LPPM Universitas Merdeka Madiun, 2018)
Development Natural Disaster Information Geografis System is a website service utilizing digital map service. To facilitate the Regional Disaster Management Agency (BPBD) and the Community of Madiun Regency in providing and receiving information about the occurrence of Natural Disasters in Madiun District, the need for the application of information systems. The information system can display the points where the Natural Disasters occur. With the Information System, everyone can see the location of the map of the disaster occurrence area along with the description of the area. in this study developed a